2014
DOI: 10.1590/0104-1169.3503.2467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of "+Contigo" training on the knowledge and attitudes of health care professionals about suicide

Abstract: OBJECTIVES: to evaluate the results of "+Contigo" training, developed by nurses and directed at 66 health professionals of integrated school health teams in Primary Health Care. METHOD: quantitative with data collection through the Suicide Behavior Attitude Questionnaire, administered before and after the training. RESULTS: significant increases were observed in suicide prevention knowledge and in changing attitudes of health professionals towards individuals with suicidal behavior. CONCLUSION: these results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
2
20
0
9
Order By: Relevance
“…Education of health professionals needs to includes skills related to self-knowledge, empathy, understanding, communication, attitudes and knowledge about suicidal behavior, (13,17) the possibility of suicide prevention, and the clarification of the role of nursing in the care of the suicidal patient. (18) Negative, moralistic, or condemnatory attitudes toward suicidal behavior are among the many factors that interfere with the quality of care for a person at risk for suicide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Education of health professionals needs to includes skills related to self-knowledge, empathy, understanding, communication, attitudes and knowledge about suicidal behavior, (13,17) the possibility of suicide prevention, and the clarification of the role of nursing in the care of the suicidal patient. (18) Negative, moralistic, or condemnatory attitudes toward suicidal behavior are among the many factors that interfere with the quality of care for a person at risk for suicide.…”
Section: Resultsmentioning
confidence: 99%
“…(13) One study identified a less moralistic attitude (15) among women, while in other investigations, there was no difference in attitudes according to sex. (13,17) Education in mental health and suicide appears to promote consistent improvements in attitude and knowledge related to suicide. (7,15) In the present study, participation in events, courses and lectures on suicide was not associated with better attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also demonstrated that interventions at the level of problem-solving and, consequently, in the acquisition/development of effective coping strategies can contribute to preventing suicidal behaviors (Santos et al, 2014). Through the intervention dynamics, adolescents begin understanding that some problem-solving strategies are more effective than others, and that these may change over time; they learn new strategies or adjust the existing ones to each situation.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 2015/2016 school year, the assessment is only performed before the intervention and at the end of the school year. The data collection instrument is a questionnaire composed of a socio-demographic characterization followed by several scales that measure variables such as well-being, coping, self-concept, and depression (Santos, Erse, Façanha, Marques & Simões, 2014).…”
Section: The +Contigo Projectmentioning
confidence: 99%
See 1 more Smart Citation